Teachers’ Voices towards HOTS Integration in Teaching Reading Comprehension - Nyimas Larasati Utami; Rita Inderawati; Eryansyah Eryansyah (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2021)
Abstract. Higher order thinking skill (HOTS) is the demanded skill in 21st century that one needs to possess in order to be able to compete in the advanced era. The aim of this case study is to investigate the teachers’ beliefs in HOTS integration in the teaching of reading comprehension as well as how the beliefs are applied in the practices of teaching reading by doing a qualitative study in a case-study design. A semi-structured interview and classroom observations were used to obtain the data. The results indicated that the teachers shared strong beliefs about the concept of HOTS and its components. The concept includes how they defined HOTS. In addition, the components revealed how they comprehend analyzing (C4), evaluating (C5), and creating (C6). Practically, the teachers' beliefs were not fully reflected, particularly in the question and assignment they assigned to students that indicated LOTS. This ivestigation suggests that more teachers’ professional development is required to promote the success of HOTS incorporation into teaching reading comprehension, mainly during online learning due to pandemic.Keywords: Higher Order Thinking Skill, HOTS, Reading Comprehension, Teachers’ Beliefs,   integration